An Analysis of the Slope Stability of Young Rock Cliffs in Sibang, Bali Using GEO5 - Nur Ayu Diana; Ganeca Efa Mareta (Media Teknik Sipil, 2024)
This study presents a comprehensive analysis of slope stability for young rock cliffs in the Sibang region of Bali, employing advanced geotechnical software GEO5. The investigation is crucial due to the dynamic geological conditions and rapid changes in land use in the area, posing potential risks to infrastructure and environmental stability. The research focuses on young rock cliffs, characterized by recent geological formations, which are inherently susceptible to slope instability. This slope stability analysis is carried out using the GEO5 auxiliary program which will produce a Safety Factor value which is used as the basis for building a construction which interprets whether the slope is safe or not. The safety factor value used as the minimum value is 1.5, so the slope must have a SF value ≥ SF min = 1.5. This analysis was carried out on 4 cross sections with 2 method which name is Morgenstern-Price and Bishop Method because the analysis carried out was complex in terms of force and moment. The Safety Factor of cross section on BH-03 to BH-01 is not safe because the value is 1,16 and 1,15 which is < 1,5 (the minimum safety factor). Therefore, the slope must modelled with terraced slopes and also retaining wall reinforcement for each modelled terrace height.